Śrī śāntasudhārasa : vistrta vivecana tathā grantha ane granthakāranā savistāra paricaya sāthe - Vinayavijaya, 17th cent (Śrī Motīcanda Kāpaḍiyā granthamāḷā ;, 1976)
Medieval work on Jain religion and philosophy; includes critical commentary.